CONTESTATION OF ISLAMISM OVER THE QUR’ANIC INTERPRETATION: A STUDY ON AL-TAFSIR AL-TAUHIDI OF HASAN AL-TURABI - Zulyadain; Syamsul Wathani; Akhmad Mughzi Abdillah (UIN Raden Mas Said Surakarta, 2022)
The purpose of this study is to examine the relationship between Islamist ideology and the birth of a tafsir. Hasan al-Turabi, an Islamic ideologue in Sudan, has a basic view of the Qur'an and his own method of interpretation in al-Tafsir al-Tauhidi. This study discovered that Islamism was perceived as a unified Islamic view based on historical dialectical perspectives and an effective historical analysis. Islamism is defined as a form of application of all Islamic values and principles, particularly in advancing social justice values, based on the perspective that the Qur'an teaches tauhid and that every verse is united. From an effective historical perspective, al-Turabi's pattern of interpretation offers methodological-material criticism of the classical and modern tafsir. His model of interpretation emphasizes the excavation of message elements and is used as a guide for living today. The Qur'an is a set of guidelines not only for faith and worship, but also for all aspects of life. As a result, Qur'anic interpretation must be consistent and founded on Qur'anic fundamental values. The presence of al-Tafsir al-Tauhidi demonstrates that al-Turabi's pattern interpretation is not independent from his intellectual, ideological, and political context in Sudan.